Study of deformation characteristics and a strain calculation model for pipelines impacted by landslides - Shi, Ning; Li, Liang-liang; Ma, Yun-bin; Li, Qiu-juan; Bai, Lu-yao (Frontiers in Earth Science, 2023)
It is not uncommon to see pipelines damaged by landslides. If the maximum strain that landslides exert on pipelines can be calculated from available survey data, then pipeline damage can be more accurately predicted and the safety of the pipeline can be improved. Furthermore, this information can assist targeted prevention and control measures, which will undoubtedly greatly reduce the risk that landslides pose to pipelines. However, although researchers have conducted considerable research on landslide-induced pipeline deformation, there is no model that can calculate the change in pipeline strain with the displacement of landslide material. In this regard, based on the geological data collected from a buried crude oil pipeline damaged by a landslide near a city in southeast China, this work uses numerical simulations to obtain the deformation parameters of pipelines affected by landslides at different orientations and for different landslide and pipeline parameters. Furthermore, this work summarizes the deformation characteristics of pipelines affected by landslides under these different variables. Finally, a model is constructed and verified that simulates the change in pipeline strain with soil displacement while considering the characteristics of the landslide mass and the pipeline itself. The results show that the model can sufficiently reflect the influence of various factors that act on pipeline deformation and can accurately calculate the maximum strain landslides exert on pipelines.